Proyeksi Pengembangan Komoditas Kelapa Dalam Secara Kewilayahan Berbasis Sumberdaya Lahan Dalam Rangka Mendukung Pembangunan Perkebunan di Kalimantan Tengah - Bhermana, Andy; Prasetiyo, Sandis; Irwandi, Dedy; Agustini, Sri (Universitas Medan Area, 2020)
The development of coconut as one of the prime commodities in Central Kalimantan is required to contribute national export needs. The results of analysis and evaluation of landsuitability indicated that at regional level of Central Kalimantan, the land suitability class for coconut is class S3 (marginally suitable). The main limiting factors found in wetland typology include presence of peat, drainage, nutrient availability and soil acidity. Whereas on dry land is soil acidity, slope and nutrient availability. The results of further spatial analysis explain that the potential areas for the coconut commodity development in Central Kalimantan is 3,499,712 Ha or 22.65% of the total areas. Spatially, the potential of development areas are spread within almost every district. There are 2 areasthat is not designated for coconut development, namely the city of Palangka Raya and Murung Raya regency due to limiting factors existence such as sandy soil type and steep slope (> 30%). Regional development strategies for coconut commodities can then beallocated to areas that have abandoned land areas. While at areas surrounding by settlements, they can be implemented by the use intercropping farming systems at the age of coconut growth for less than 3 years n order to optimize the land resources and climate productivity while at the same time increasing the income.